Reliability in the evaluation of international and national judges in an artistic swimming routine - Katia Regina Ponciano; Meico Fugita; Cláudia Borim da Silva; Roberta Luksevivius Rica; Ana Carolina Gomes; Cássio de Miranda Meira Júnior; Danilo Sales Bocalini (Universidade Federal de Santa Catarina, 2021)
Artistic swimming (AS) is a sport evaluated by fifteen judges in routine sessions. The athletes' goal is to achieve proficient motor patterns according to pre-established criteria. The present studied analyzed whether there is difference between the two groups of AS judges with different levels of experience. The group of the International Swimming Federation - FINA (IG) evaluates AS at national and international level and the non-FINA group (NG) evaluates AS only at national level. Twenty experienced judges were divided into groups, 10 IG judges and 10 NG judges. Thus, judges evaluated the item execution of three routines with five required elements. Cronbach's alpha coefficient showed high internal consistency in IG (a= 0.85 in T1 and 0.83 in T2). In NG, internal consistency was observed in T1 and low consistency in T2 (a= 0.82 in T1 and 0.39 in T2). Evaluation analysis between IG and NG was significant (p˃0.0330) and reliability analysis (bias: -0.1266 95% agreement limit: -1.642 to 1.388) showed consistency and high degree of confidence in results. The findings suggest that the item execution of required elements showed high objectivity regarding judges with different levels of experience, IG and NG, regardless of categorization and time of practice. FINA has changed the number of judges and the number of items evaluated in routine sessions. It is suggested that the reduction of items has contributed in a positive way so that judges can focus more on evaluation itself.